Favorable outcome of experimental islet xenotransplantation without immunosuppression in a nonhuman primate model of diabetes - Ludwig, B.; Ludwig, S.; Steffen, A.; Knauf, Y.; Zimerman, B.; Heinke, S.; Lehmann, S.; Schubert, U.; Schmid, J.; Bleyer, M.; Schönmann, U.; Colton, C.; et al. (National Academy of Sciences, 2017)
© 2017, National Academy of Sciences. All rights reserved. Transplantation of pancreatic islets for treating type 1 diabetes is restricted to patients with critical metabolic lability resulting from the need for immunosuppression and the shortage of donor organs. To overcome these barriers, we developed a strategy to macroencap-sulate islets from different sources that allow their survival and function without immunosuppression. Here we report successful and safe transplantation of porcine islets with a bioartificial pancreas device in diabetic primates without any immune suppression. This strategy should lead to pioneering clinical trials with xenotransplantation for treatment of diabetes and, thereby, represents a previously unidentified approach to efficient cell replacement for a broad spectrum of endocrine disorders and other organ dysfunctions.